Analysis of Procrastination in Completing Final Assignments (Case Study of UMS Faculty of Teacher Training and Education Students, Class of 2017) - Febriyanti, Nofia Mega; Mustofa, Rochman Hadi (Proceedings International Conference on Education Innovation and Social Science, 2025)
Students have activities related to both academic and non-academic matters, so they are required to manage these activities well. Students who do not complete their final assignments within the recommended timeframe are said to be procrastinating, as this occurs in relation to writing their final assignments. They often experience problems requiring a long time, due to difficulty managing time between meeting with lecturers and working, resulting in delays in completing their final assignments. This study aims to determine procrastination patterns among students of the 2017 intake of the Faculty of Teacher Training and Education, Universitas Muhammadiyah Surakarta. The method used is a qualitative case study approach, located at Universitas Muhammadiyah Surakarta. Data were collected through in-depth interviews with informants.